Prophylactic use of Midazolam, Ketamine, and Ketamine plus Midazolam for prevention of perioperative shivering during spinal anaesthesia in patients undergoing infraumbilical surgeries: a comparative study - Kumar, Manoj; Kumar, Ankur; Singh, Dheer; Saxena, Surekha (International Journal of Research in Medical Sciences, 2017)
Background: Shivering is a common problem faced by an anaesthesiologist during perioperative period. Shivering occurs during both general anaesthesia and regional anaesthesia but it is more troublesome during neuraxial anaesthesia. To evaluate the effectiveness of intravenous Midazolam, Ketamine and combination of Midazolam with Ketamine in control of shivering. Methods: The study was conducted in 90 ASA I and II patients receiving neuraxial anaesthesia with comparable dose of hyperbaric bupivacaine. The patients were allocated in three groups of 30 each to receive Midazolam 75 mcg/kg, ketamine 0.5 mg/kg and Midazolam 37.5 mcg/kg plus Ketamine 0.25 mg/kg IV after the appearance of shivering. Disappearance and recurrence of shivering as well as temperature and haemodynamics were recorded with scheduled intervals. Results: IV Midazolam plus Ketamine at the dose of 37.5 mcg/kg and 0.25 mg/kg is more effective in prophylaxis of shivering than IV Midazolam 75 mcg/kg or IV Ketamine 0.5 mg/kg. Small number of patients showed, clinically as well as statistically insignificant, incidence of hypotension, bradycardia and respiratory depression of various degrees at various time intervals. Conclusions: Thus, IV Midazolam plus Ketamine at the dose of 37.5 mcg/kg and 0.25 mg/kg IV is more effective in prophylaxis of shivering than IV Midazolam 75 mcg/kg or IV Ketamine 0.5 mg/kg following subarachnoid blockade for infra umbilical surgery. The side effects like Hypotension, nausea, vomiting and pruritus are also very less with combination and prove that it is a better agent for prophylaxis of shivering following regional anesthesia.